Celebrity influence and consumer’s buying intentions: a cross-cultural comparison between Australia and Singapore - Moraes, Marcela; Goutas, John; Gountas, Sandra (2016)
Societies have always had a need for heroes to define new heights of achievements, new thresholds of ability, endurance and aspirations. Different societies around the world produced different types of heroes and famous people with varying representations of complex aspirational roles and behaviours for the followers to emulate. Famous people and celebrities have been globally used to endorse various products. Research findings suggest that celebrities can be effective catalysts of influence to overcome cultural barriers for global brands. This cross cultural study explores the differences of Australian and Singaporean consumer purchase intentions as a result of celebrity influence. The results support the hypotheses that consumer intention to buy an endorsed brand is influences by consumer aspirations and need for fame which is mediated by their favourite celebrity’s personality and lifestyle attributes. Managerial implications for international marketing are discussed.